Utilization of Neuromarketing Principles in Visual Communication Design to Increase Consumer Attraction - Paramitha, Jessica (Green Publisher Indonesia, 2024)
Neuromarketing, a discipline combining neuroscience and marketing, has become a primary focus in understanding consumer behavior through understanding the brain's response to marketing stimuli. This article explores the development of neuromarketing in visual communication design, investigating the neuroimaging techniques used in neuromarketing and case studies illustrating its application in optimizing visual design. Neuroimaging techniques, such as fMRI and EEG, enable researchers to monitor brain activity related to responses to visual stimuli. Case studies show that manipulating visual designs can trigger positive brain responses, increase ad attractiveness, and influence consumer behavior. In addition to its benefits, the application of neuromarketing also faces several challenges, including the complexity of interpreting neuroimaging data and limitations in generalizing research findings. However, these challenges can be overcome with a holistic approach and collaboration among neuroscientists, marketers, and designers.